2012
DOI: 10.1086/665924
|View full text |Cite
|
Sign up to set email alerts
|

Performance Modeling for the RAVEN Multi-Object Adaptive Optics Demonstrator

Abstract: RAVEN will be a Multi-Object Adaptive Optics (MOAO) technology and science demonstrator on the Subaru telescope. The baseline design calls for three natural guide star (NGS) wavefront sensors (WFS) and two science pickoff arms that will patrol a ∼2′ diameter field of regard (FOR). Sky coverage is an important consideration, because RAVEN is both a technical and science demonstrator. Early-stage simulation of RAVEN's performance is critical in establishing that the key science requirement can be met. That is, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…This phenomenon is linked to the variation of the optical disturbances across the field and is characterized by the anisoplanatic angle, θ 0 ∝ λ 6∕5 , typically of the order of tens of arcseconds in the H band [1].…”
Section: Multi-object Adaptive Opticsmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon is linked to the variation of the optical disturbances across the field and is characterized by the anisoplanatic angle, θ 0 ∝ λ 6∕5 , typically of the order of tens of arcseconds in the H band [1].…”
Section: Multi-object Adaptive Opticsmentioning
confidence: 99%
“…(12) is further explored in Section 4.A for the Raven demonstrator [1]. When phase is expanded onto the Zernike polynomials, the SA cross-covariance functions can be analytically computed for the infinite outer-scale case of turbulence [14,15]:…”
Section: A Equivalent Tomographic Reconstructorsmentioning
confidence: 99%
“…The Raven error budget and performance modeling estimates are presented in detail elsewhere 10 . In summary, by choosing WFSs with 10x10 subapertures and 0.4 arcseconds/pixel and DMs with 11x11 actuators in the pupil, we showed that while the bestcase AO performance of Raven is lowered, performance will be limited by tomographic and WFS noise errors due to the low density of bight NGSs for most Raven science cases.…”
Section: Modelingmentioning
confidence: 99%
“…In these simulations, we were only concerned with the wavefront error (WFE) due to WFS spot sampling and centroiding method. For faint stars, we assumed an integration time of 5.5 ms (180 Hz sampling frequency), so some additional WFEs due to lag will be incurred 10 . The Raven WFSs will accept light between 600 and 900 nm so we also assume a flat spectrum (V-R=0 color) for the NGS to calculate the total photon counts.…”
Section: Modelingmentioning
confidence: 99%
“…Multi-object adaptive optics (MOAO) is one of these techniques [10,11]. CARMEN is a MOAO reconstructor created at the University of Oviedo.…”
Section: Introductionmentioning
confidence: 99%